Jennifer Duprey, «The Aesthetics of the Ephemeral. Memory Theaters in Contemporary Barcelona», State University of New York, 2014, 274 pp. - Amo Sánchez, Antonia (Caplletra. Revista Internacional de Filologia, 2016)
Ressenya sobre el llibre de Jennifer Duprey, The Aesthetics of the Ephemeral. Memory Theaters in Contemporary Barcelona, State University of New York, 2014, 274 pp.